DEVELOPMENT OF PICTORIAL-BASED FIVE-TIER MULTIPLE CHOICE DIAGNOSTIC TEST TO IDENTIFY MISCONCEPTIONS OF ELECTROCHEMICAL CELL MATERIAL - Ulya, Nur Afni Himmatul; Rahmawan, Setia (Universitas Muhammadiyah Mataram, 2025)
Abstrak: Miskonsepsi dalam pembelajaran kimia, khususnya pada sel elektrokimia seperti sel volta dan elektrolisis, sering terjadi karena kompleksitas konsep redoks, perpindahan elektron, serta proses di anoda dan katoda. Penelitian ini bertujuan mengembangkan instrumen tes diagnostik five-tier multiple choice berbasis pictorial untuk mengidentifikasi miskonsepsi pada materi ini. Metode yang digunakan adalah Research and Development (R&D) model Tessmer, yang terdiri dari lima tahap: preliminary, self-evaluation, expert review, one-to-one evaluation, dan small group evaluation. Validitas diuji menggunakan Content Validity Ratio (CVR) dan Content Validity Index (CVI), sementara reliabilitas diuji dengan model Rasch. Hasil penelitian menunjukkan bahwa instrumen ini valid (CVI rata-rata 1,00) dan memiliki reliabilitas sedang (Cronbach’s Alpha 0,71-0,76). Instrumen ini berhasil mengidentifikasi miskonsepsi terkait prinsip kerja sel volta, elektrolisis, dan arah aliran elektron. Mayoritas peserta didik mengandalkan internet sebagai sumber utama informasi, tetapi kurangnya verifikasi memperbesar potensi miskonsepsi. Instrumen ini diharapkan membantu guru dalam menyusun strategi pembelajaran berbasis data untuk meningkatkan pemahaman peserta didik.Abstract: Misconceptions in chemistry learning, particularly in electrochemical cells such as voltaic cells and electrolysis, often arise due to the complexity of redox concepts, electron transfer, and processes occurring at the anode and cathode. This study aims to develop a pictorial-based, five-tier multiple-choice diagnostic test to identify misconceptions in this subject. The method used follows the Research and Development (R&D) approach based on the Tessmer model, which consists of five stages: preliminary analysis, self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Validity was assessed using the Content Validity Ratio (CVR) and Content Validity Index (CVI), while reliability was tested using the Rasch model. The results indicate that the instrument is valid (average CVI = 1.00) and has moderate reliability (Cronbach's Alpha = 0.71–0.76). It successfully identifies misconceptions related to the working principles of voltaic cells, electrolysis, and the direction of electron flow. The majority of students rely on the internet as their primary source of information; however, the lack of verification increases the risk of misconceptions. This instrument is expected to help teachers design data-driven learning strategies to enhance students' understanding.